THE CHARACTERISTICS OF CULTURE-BOUND SYNDROME OF ACEHNESE SPEAKERS IN A SOCIOPSYCHOLINGUISTICS PERSPECTIVE - Budi Rizka; Lismalinda Lismalinda (Getsempena English Education Journal, 2022)
This study aims to classify the characteristics of Culture-Bound Syndrome in Acehnese speakers from the perspective of Socio-Psycholinguistics, particularly in Aceh Besar, Pidie, and Aceh Utara by comparing gender, age, and the education level of the patient. The researchers chose to use a case study approach to conduct data to be able to provide an overview of the characteristics of Culture-Bound Syndrome behaviour displayed. In analysing the data, the researcher refers to Spradley Theory who said that analytical technique with four advanced paths, namely (1) domain analysis; (2) taxonomy analysis; (3) componential analysis; and (4) cultural values ​​analysis. After the research done, the researchers found that the characteristics of Culture-Bound Syndrome in Acehnese speakers are five characteristics, namely (1) Coprolalia, this research found that females more often use Coprolalia than males, more often in adult patients than in adolescents and elderly patients, and only appeared in patients with a low level of education; (2) Echolalia was found in adolescents, adults and the elderly, more often in female patients than in male, and more often used by lower education level than high level of education; (3) Auto Echolalia was only appears of females while in males and elder it is not found. Meanwhile, the most Auto Echolalia were found at adolescents than adults. If we look at the aspect of education level, the patients with a low education level more often than higher education level; (4) Auto Obedience was not found at category of females and adolescents; and (5) Religio was only appears in category of adult, elderly, males, and higher education levels. The last characteristic has never existed in the results of previous research studies, therefore, there is a need for a more in-depth study with a larger scope to examine this section.